Empowerment‐based education for established type 2 diabetes in rural England. (April 2017) - Akhter, Kalsoom; Bunn, Christopher; Graffy, Jonathan; Donald, Sarah; Ward, Candice; Simmons, David
Abstract: People with newly‐diagnosed type 2 diabetes are offered structured education, but there are few programmes for those with established diabetes. The empowerment‐based education approach from the United States has been advocated as one approach that supports self‐management, but is not used in England. The aim of this study was to assess the acceptability of empowerment‐based diabetes education for patients with established type 2 diabetes. One 3.5‐hour workshop was offered to participants joining a trial of peer support in rural Cambridgeshire, UK. Four main aspects of self‐care (carbohydrates and portion size; truths and myths about diabetes; know your numbers and medications; keeping active and foot care) were addressed, followed by a question and answer session. Change in diabetes knowledge and participant perspectives were evaluated using questionnaires. Qualitative evaluation was by ethnographic observation of sessions. Patient expectations were met in 93.5% of participants. Aspects thought to be particularly useful related to diet and carbohydrates and also medications. Ethnography revealed five main themes: diet, group process, health service experience, within session peer support, and educator clinical grounding. Sixty percent of those participating increased their ability to answer diabetes knowledge‐based questions. Adopting the 'empowerment approach' is a valid method of diabetes education for those with established type 2 diabetes in England. Delivery by experienced educators is important to address queries that arise during the sessions. Copyright © 2017 John Wiley & Sons.